The moderating effect of team familiarity and similarity on virtuality and conflict in teams - Kang, Wan Lin (2010)
This article explores the influence of four moderators (member familiarity, work habits similarity, gender similarity and ethnicity similarity) on the relationship between the level of virtuality and conflict (task conflict, relationship conflict, process conflict) experienced in teams. Results from 50 student teams suggest that both member familiarity and ethnicity similarity are positive moderators of the relationship between virtuality and all conflict types. They also suggest that the relationship between virtuality and relationship conflict is positively moderated by gender similarity, but is not moderated by work habits similarity.